The role of oxidative stress, glucocorticoid receptor and ARMC5 in lipid metabolism - Yosuke Okuno; Atsunori Fukuhara; Iichiro Shimomura (Endocrine Journal)
Lipid metabolism includes lipogenesis, lipolysis, and cholesterol metabolism and it exerts a wide range of biological effects. We previously found novel roles of adipocyte oxidative stress in diet-induced obesity, adipocyte glucocorticoid receptor in Cushing syndrome, and ARMC5 in adrenocortical cells. Using genetically modified mice in which oxidative stress was eliminated or augmented specifically in adipose tissues, we have been able to elucidate that obesity-induced oxidative stress inhibited healthy adipose expansion and ameliorated insulin sensitivity. Using adipocyte-specific glucocorticoid receptor knockout mice, we found that glucocorticoids also inhibited healthy adipose expansion and decreased insulin sensitivity. This was partly due to the transcriptional upregulation of ATGL. We identified ARMC5 as a novel ubiquitin E3 ligase of full-length SREBF, a master regulator of lipid metabolism. In adrenocortical cells, ARMC5 suppresses SREBF2 activity, and loss of ARMC5 may lead to cholesterol accumulation and the development of primary bilateral macronodular adrenal hyperplasia.